The Communication of Value Judgements and its Effects on Climate Scientists' Perceived Trustworthiness. Issue 8 (17th November 2022) - Cologna, Viktoria; Baumberger, Christoph; Knutti, Reto; Oreskes, Naomi; Berthold, Anne
ABSTRACT: Scientists are called upon by policymakers to provide recommendations on how to address climate change. It has been argued that as policy advisors, scientists can legitimately make instrumental value judgements (recommendations based on defined policy goals), but not categorical value judgements (challenge and/or redefine established policy goals), and that to do otherwise is to overstep in ways that may threaten their perceived trustworthiness. However, whether these types of value judgements affect public trust in scientists remains largely untested. We conducted two studies (N1  = 367, N2  = 819) to investigate public perceptions of trustworthiness of a climate scientist expressing either an instrumental or a categorical value judgement. We found no difference in perceived trustworthiness between the two conditions. However, trustworthiness perceptions in both studies depended on individuals' support for the policy recommended by the scientist. Our findings suggest that climate scientists should not fear for their overall perceived trustworthiness when making categorical value judgments if their opinions are supported by the majority of the public.